Analysis of Generation and Composition of Domestic Solid Waste at the dr. R. Soedjono Regional General Hospital, East Lombok - Safitri, Rinjani Yulia; Suripto, Suripto; Dujana, Lalu Muhammad Aby (Jurnal Biologi Tropis, 2025)
The dr. R. Soedjono Regional General Hospital Selong East Lombok is a government-owned health service facility that has experienced an increase in accreditation status to a class B hospital. The calculation of waste generation and waste sorting at the hospital has never been carried out so that the waste management team cannot determine a waste management strategy. Therefore, it is necessary to conduct research to analyze waste generation at the dr. R. Soedjono Regional General Hospital, East Lombok. A preliminary survey was conducted to determine the techniques and schedule for collecting waste data and waste producers. Waste data collection was carried out using the load count method every day for eight days. Data collection on the daily number of people producing waste was carried out through document searches. The waste producers in question include employees, medical personnel, patients and visitors. Data were analyzed descriptively to describe waste generation and its composition. The results show that the generation of domestic solid waste at the dr. R. Soedjono Regional General Hospital, East Lombok, which was observed every day for eight days was 0.3705 kg/person/day. Waste generation fluctuates every day of the week and the highest waste generation occurred on Sundays (holidays), where the number of people producing waste was dominated by patient visitors. Domestic solid waste in the hospital is dominated by plastic waste (36%), leftover food and leaves (31%), paper (15%) and other (11%). Others include diapers, sanitary napkins and bandages. Other waste components that were also found but with a much smaller weight percentage were wood, fabric or textile, metal and glass.